Analysis of guyed masts by the stability functions based on the Timoshenko beam-column. (1st December 2017) - Páez, Pablo M.; Sensale, Beradi
Highlights: An analytical method for calculating the guyed towers is proposed. The tower is modeled as a continuous beam-column. The method take into account the second order deformations and the shear deformations. The second order effects are calculated by the stability functions. The proposed method are sufficiently accurate compared to the finite element method. This confirm the validity of the hypotheses adopted in the development of the method. Abstract: A new formulation for the analysis of guyed towers in which the mast is modeled as a continuous equivalent beam-column on non-linear elastic supports, is proposed. Because second-order effects must not be neglected and given the importance of consider the shear deformation in the analysis of this type of structures, the method proposes the calculation of the second-order deformation using the stability functions based on the Timoshenko beam column. The equivalent beam-column properties of the mast are calculated depending on the pattern construction of the tower and the guys are replaced by non-linear elastic supports. Based on the catenary configuration of the cable, the spring constant is obtained from the secant modulus of the cable. In order to validate the proposed method, a comparative study is carried out analyzing a guyed mast using the proposed method and a numerical model through the use of finite elements. As a main conclusions we will mention that, the proposed method are sufficiently accurate compared to the finite element method, confirming the validity of the hypotheses adopted in the development of the method and; the reduction of the computational effort, since the structure does not need to be discretized into a large number of elements for the convergence.